Finite element tearing and interconnecting for the electromagnetic vector wave equation in two dimensions - Marchand, Renier Gustav (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.